Alport Syndrome: case report and review of ocular manifestations - Jain, Charu; Malik, VK; Kamboj, Reny; Kumar, Sanjeev; Kumar, Sandeep; Jain, Kirti (Nepalese Journal of Ophthalmology, 2011)
Background: Alport Syndrome is an uncommon disease. Case: We report a case of a young Indian male who presented with the characteristic ocular findings and systemic features of Alport Syndrome. Conclusion: Any young patient with a chronic renal disease should have a careful ophthalmologic examination for Alport Syndrome. Key words: Alport Syndrome, hereditary nephritis, lenticonus, deafness, retinopathy DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5275 Nepal J Ophthalmol 2011; 3(2): 188-190